NUTRITIONAL SUPERIORITY OF SEAWEED BASED ORGANIC GREEN LEAFY VEGETABLE, AMARANTHUS RETROFLEXUS L. - KUMARESWARI. T,; MARIA VICTORIAL RANI. S, (International Journal of Pharma and Bio Sciences, 2016)
One of the most important challenges for agriculture, besides enhancing food production, is to provide almost all the essential minerals and organic nutrients to humans for maintenance of health and proper organ function through organic farming. In this study seaweed liquid fertilizer (SLF) of Hypnea musciformis was used as an organic fertilizer and studied its influence on nutritional status of the leaves of Amaranthus retroflexus L. There were eighteen amino acids found in treated and control plants. Essential amino acids viz., leucine, isoleucine, valine, lysine, threonine, tryptophan, methionine, phenylalanine and histidine were found in both control and treated plants. Moreover these amino acids except leucine, lysine and threonine were found plenty in treated plants. Phenylalanine, methionine and tryptophan were respectively 236%, 107% and 107% higher than that of control. Nonessential amino acids were slightly higher than control except tyrosine and proline. Water soluble vitamins (B1, B2, B3, B6, B9, B12 and vitamin C) and fat soluble (A, D, E, K) vitamins were found to be increased in treated plants than control. The results clearly indicated that SLF of Hypnea musciformis (Wulfen) J.V. Lamouroux, an eco-friendly cost effective biostimulant, could be used as an organic supplement for improving nutritional status of vegetable crops.